Turnover of Registered Nurses in Israeli Hospitals: A Secondary Analysis from a National Survey - Toren Orly; Zelker Revital; Lipschuetz Michal; Riba Shoshana; Reicher Sima; Nirel Nurit (International Journal of Translational Research, 2017)
Aim: To assess the extent and directions of internal hospital turnover of registered nurses and to examine the associated factors and stressors. Background: Internal turnover of hospital nurses is mainly horizontal. Occurring on a large scale, it could lead to dropout of skilled personnel, burdening hospitals both financially and in terms of human resources, affecting the quality of care. Methods: A secondary analysis based on data from the national study on
Keywords: Obesity